Genetic diversity analysis and molecular characterization of grain amaranth genotypes using inter simple sequence repeat (ISSR) markers - Mayuri J. Gelotar; Darshan T. Dharajiya; S. D. Solanki; N. N. Prajapati; Kapil K. Tiwari (Bulletin of the National Research Centre, 2019)
Abstract Background Grain amaranth (Amaranthus spp.) has been cultivated since ancient times in some countries in the world and it is one of the oldest food crops. At present, the crop has gained more importance in the plains of India, especially in parts of Gujarat and Maharashtra. Grain amaranth exhibits an incredible extent of morphological diversity and an extensive adaptability to diverse eco-geographical conditions. Hence, the aim of the recent research was to evaluate the genetic diversity of 19 genotypes from four diverse species of Amaranthus from India using ISSR markers. Results The set of 11 polymorphic ISSR primers produced a total of 114 amplicons, among which 98 amplicons were polymorphic. The mean number of polymorphic amplicons per primer was 8.91. Overall, the size of PCR-amplified DNA fragments ranged from 200 to 3702 bp. The average percent polymorphism was 87.15%, and the average PIC value was 0.853, which indicates good selection of primers in the present study for the assessment of genetic diversity. The unique amplicon (marker)-producing primers were also found which can be used for identification of genotypes. The dendrogram grouped 19 grain amaranth genotypes into two major clusters. The groups formed on the principle component analysis (PCA) plot resembles with the results of the dendrogram although some genotypes have been diverted on the PCA plot. Conclusions The technique may be used to obtain reasonably precise information on the genetic relationship among grain amaranth genotypes. Such information may be useful for selecting the diverse parents and monitoring the genetic diversity periodically in the breeder’s working collection of grain amaranth.